2020
DOI: 10.1002/qua.26154
|View full text |Cite
|
Sign up to set email alerts
|

Study on the normalized Laplacian of a penta‐graphene with applications

Abstract: Let L n denote a linear pentagonal chain with 2n pentagons. The penta‐graphene (penta‐C), denoted by R n is the graph obtained from L n by identifying the opposite lateral edges in an ordered way, whereas the pentagonal Möbius ring Rn′ is the graph obtained from the L n by identifying the opposite lateral edges in a reversed way. In this paper, through the decomposition theorem of the normalized Laplacian characteristic polynomial and the relationship between its roots and the coefficients, an explicit closed‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…In this paper, motivated by previous studies 19–23 and by using the Laplacian decomposition theorem, we achieved the explicit closed‐form formulations for normalΩ$$ \Omega $$ and τ$$ \tau $$ on n$$ {\triangle}_n $$.…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, motivated by previous studies 19–23 and by using the Laplacian decomposition theorem, we achieved the explicit closed‐form formulations for normalΩ$$ \Omega $$ and τ$$ \tau $$ on n$$ {\triangle}_n $$.…”
Section: Introductionmentioning
confidence: 99%
“…In [24], Guo and Dong, gave the energy and analytical applications of chemical graphs. Li et al [25] used some matrix techniques to obtain the eigenvalues and their multiplicity to fnd the kirchhof index. In [26], Khan et al, established someproperties and applications of toxicities.…”
Section: Introductionmentioning
confidence: 99%
“…Existing studies have demonstrated that calculations of the Laplacian eigenvalues face an enormous challenge because the eigenvalues are dominated by the network topology [9][10][11]. It is of interest to explore diverse methods to reveal the correlation between the topology and the coherence [12,13].…”
Section: Introductionmentioning
confidence: 99%